Meta-Analysis Effectiveness of Using the Discovery Learning Model on Students’ 21st-Century Critical Thinking Skills - Sri Handayani Rahayuningsih; Asrowi; Gunarhadi; Murni Ramli (Jurnal Penelitian Pendidikan IPA, 2024)
Critical thinking skills greatly support students to think analytically, thus making themselves intelligent. Two factors influence students' critical thinking skills, including the first from teacher resources. This study aims to determine empirical data related to the effectiveness of using the Discovery Learning Model for students. The method used is meta-analysis, namely a statistical review by analyzing the results of research published internationally related to the use of the Discovery Learning model on critical thinking skills. The analysis sample consists of 4 international journals published in 2017 - 2022 at the high school level, which discuss the writing of experiments on the effectiveness of using the Discovery Learning model on critical thinking skills. The writing instrument is in the form of a coding sheet that summarizes journal data and information. Based on the analysis of the overall influence value, the average value of the effectiveness effect is ≥ 0.8, which means it is in the large effect category. The findings of the analysis also show that the effectiveness of using the Discovery learning model affects increasing critical thinking skills compared to conventional methods. This provides the conclusion that the use of the Discovery Learning model on critical thinking skills is effective in learning.